A methodological model for ecogeographic surveys of crops - Guarino, Luigi; Maxted, N.; Chiwona, E.A. (2005)
In this paper authors discuss how to adapt the methodology of wild plant ecogeographic studies when dealing with cultivated species. They show that the model presented by Maxted et al. 1995), with a few changes in emphasis and detail, proves robust enough to be applied to crops. Particular focus has been placed on various countries in southern and eastern Africa. An attempt was made to review both on-line information sources and conventional literature.